Drivers of Gross Capital Inflows : Which Factors Are More Important for Sub-Saharan Africa? - Calderon, Cesar (World Bank, Washington, DC, 2019)
This paper discusses recent trends and investigates the drivers of capital flows across regions in the world, with emphasis on Sub-Saharan Africa. The post-global financial crisis behavior of capital flows into Sub-Saharan Africa is unique and differs from that of global capital flows. The structure of financial flows into Sub-Saharan Africa has shifted toward new sources, such as international bond issuances and debt inflows from non–Paris Club governments. The main message is that the behavior of capital flows into Sub-Saharan Africa differs from that of capital flows into global, industrial, and non–Sub-Saharan African developing countries. The regression analysis reveals that gross flows into Sub-Saharan African are predominantly influenced by external factors, such as foreign growth and uncertainty in global markets and policies. Capital flow behavior for Sub-Saharan African countries is different from that of industrial countries due to different economic structures, which render different transmission processes. The main findings suggest that pull and push factors are the driving forces of capital inflows for industrial countries and non–Sub-Saharan African developing countries—especially better economic performance, sound fiscal outcomes, a greater degree of financial openness, and stronger institutions. The impact of these drivers has become stronger in the 2000s. Macroeconomic policy can play an important role in attracting capital inflows. For instance, fiscal discipline promotes greater other investment inflows, and less flexible exchange rate arrangements (more exchange rate stability) foster portfolio investment inflows.